Phatic Marker in Bengkulu Malay Language - Eli Rustinar; Cece Sobarna; Wahya Wahya (JURNAL ARBITRER, 2020)
The current study aims to describe the form and function of a phatic marker in Bengkulu Malay. The data were taken from the spoken language of Bengkulu Malay language, which consists of phatic utterances. The data were collected using the observational and conversational method. The analysis was done using contextual analysis, distributional method, and pragmatic identity method. The result shows there are two forms of phatic in Bengkulu Malay, they are particle form, including ‘nah’, yak ‘yah’, ay ‘ai’, way ‘wai’, awu ‘ya’, woy ‘woi’, wey ‘wei’, hoy ‘hoi’, and clitic form, including -lah and ‘lah’.